China's emerging middle class beyond economic transformation - edited by Cheng Li (Washington, D.C Brookings Institution Press, 2010)
The rapid emergence and explosive growth of China's middle class have enormous consequences for that nation's domestic future, for the global economy, and for the whole world. In China's Emerging Middle Class, noted scholar Cheng Li and a team of experts focus on the sociopolitical ramifications of the birth and growth of the Chinese middle class over the past two decades.
Includes bibliographical references (p. 359-372) and index.
Keywords: Middle class--China.